Health Education at SDN 2 Sinarjaya Garut, in The Context of Introducing The Concept of Balanced Nutrition - Lubis, Novriyanti; Lindayani, Lindayani; Hidayat, Syaiful; Putri, Regina; budiman, Virly oktaviani; Santi, Rahmania; lisiawan, Bulan esaura; Patmawati7, Pipit; Fauzi, Rifki (Fakultas Kewirausahaan Universitas Garut, 2024)
The extension activity was located at SD Negeri 2 Sirnajaya Garut with the theme